Dynamics of Strategies-based Language Instruction: A Study of Reading Comprehension and Problem Solving Abilities via Structural Equation Modeling. - Ghahari, Shima; Basanjideh, Mahin (RELC Journal, 2015)
The study aimed at exploring the psychological as well as educational outcomes of strategies awareness and use. We set out to examine the effect of reading strategic investment on language achievement and problem solving ability (PSA). The participating EFL learners were heterogeneous in terms of reading instruction; two of the intact groups had received normal instruction studying selected short stories with a primary focus on vocabulary development and comprehension check, whereas the second group had been trained under a strategies-based instruction over two consecutive semesters by one of the researchers. A descriptive data collection procedure and follow-up exploratory and confirmatory analyses revealed metacognitive and cognitive strategies positively affect the enhancement of PSA and reading comprehension achievement (RCA). It was found, however, that metacognitive strategies are more effective for the development of PSA whereas cognitive strategies contribute to RCA more than their metacognitive counterparts.